2012
DOI: 10.3382/ps.2012-02655
|View full text |Cite
|
Sign up to set email alerts
|

Modified-atmosphere packaging of hen table eggs: Effects on pathogen and spoilage bacteria

Abstract: As part of a more comprehensive research activity on the use of modified-atmosphere packaging for the improvement of quality and functional properties of table eggs, the effects of air, 100% CO(2), and 100% O(2) packaging were also evaluated on the survival of experimentally inoculated pathogen bacteria (Salmonella Enteritidis, Escherichia coli, and Listeria monocytogenes) as well as on spoilage bacteria (total aerobic mesophilic bacteria) on table eggs during 30 d of storage at 4, 25, and 37°C by colony count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…2 log 10 CFU/g after 28 days of storage at 21°C (Figure 1). On the contrary 100% CO 2 packaging did not impact significantly on the load of total bacteria as well as total and faecal coliforms confirming previously reported results (Pasquali et al, 2012) The weight loss of eggs during storage is mainly caused by evaporation of water and loss of CO 2 (Caner, 2005). A significant different weight loss was registered comparing 100% CO 2 packed eggs and unpacked eggs (1.5 vs 7%).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…2 log 10 CFU/g after 28 days of storage at 21°C (Figure 1). On the contrary 100% CO 2 packaging did not impact significantly on the load of total bacteria as well as total and faecal coliforms confirming previously reported results (Pasquali et al, 2012) The weight loss of eggs during storage is mainly caused by evaporation of water and loss of CO 2 (Caner, 2005). A significant different weight loss was registered comparing 100% CO 2 packed eggs and unpacked eggs (1.5 vs 7%).…”
Section: Discussionsupporting
confidence: 77%
“…In packed eggs the values reported in the present study are slightly higher than those previously reported [1.5% this study vs 0.5% Rocculi et al (2009)]. Differences in weight loss between studies may be due to the storage conditions, temperature, egg size and shell porosity as well as, for packed eggs, inclusion of moisture adsorbent (Bhale et al, 2003;Caner, 2005;Rocculi et al, 2009;Pasquali et al, 2012).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The relative abundance of Bifidobacterium in the 4 °C sample (17.72% that in the 10 °C sample (7.10%). It has been reported that Bifidobacteri nistic effect on the growth and reproduction of other bacteria [53], whi relatively to extending the shelf life of LEW under a storage temper accepted that Escherichia is an important contributor to the spoilage of rived products [54]. In the present study, Escherichia appeared at a rel dance in the two groups, though especially in the 4 °C sample.…”
Section: Bacterial Abundance and Distributionmentioning
confidence: 38%